G-D’s Physics”: On the True Nature, Elegance & Purpose of the Universe! - Bentovish, Jehonathan (European Journal of Applied Sciences, 2023)
Twenty-first century Theoretical Physics has undergone a major “Paradigmatic-Shift” from the Old “Material-Causal” Paradigm of GRT & QM to the New “G-D’s Physics” Scientific Paradigm pointing at the existence of a singular higher-ordered “Universal Computational/Consciousness Principle” (UCP) that simultaneously computes all exhaustive spatial pixels in the universe at the incredible rate of “c2/h” = 1.36-50 sec’(!), thereby producing an extremely rapid series of “Universal-Frames” (UF’s) of the whole physical universe at any “minimal time point”! Two unique “Critical Predictions” of this New “G-D’s Physics” Paradigm have been empirically validated as “more valid” than the corresponding predictions of both GRT & QM, thereby establishing it as the New Scientific Paradigm for 21st Century Physics! Indeed, this New “G-D’s Physics” Scientific Paradigm was shown successful not only in being able to unify between GRT & QM but also (for the first time in Physics) between the four basic physical features of “space”, “energy”, “mass” and “time” based on this singular higher UCP! Accordingly, “G-D’s Physics” postulation of the UCP’s “Ten Hierarchical Computational Dimensions” (THCD’s) that have “preplanned” the whole creation and development of the entire physical universe from “inanimate” matter through “animate”: plants, animals and human-beings – leading up to “Ultimate Perfected Geualh Goal State”, e.g., in which Humanity (and Science) recognize the singularity of this UCP and its “intrinsic-sublime” characteristics of “Morality”, “All-Goodness”, “Peace” and “Harmony” etc., thereby brining Humanity to its current (beginning of) this Ultimate Perfected Geulah State!